Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.3389/fonc.2022.973104
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of non-enhanced computer tomography-based radiomics for predicting hematoma expansion: A meta-analysis

Abstract: BackgroundThis meta-analysis aimed to assess the efficacy of radiomics using non-enhanced computed tomography (NCCT) for predicting hematoma expansion in patients with spontaneous intracerebral hemorrhage.MethodsThroughout the inception of the project to April 11, 2022, a comprehensive search was conducted on PubMed, Embase, and Cochrane Central Register of Controlled Trials. The methodological quality of studies in this analysis was assessed by the radiomics quality scoring system (RQS). A meta-analysis of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 38 publications
(47 reference statements)
0
2
0
Order By: Relevance
“…Several studies have suggested that PHE formation, inflammation, and HE are linked ( Alvarez-Sabín et al, 2004 ; Silva et al, 2005 ; Florczak-Rzepka et al, 2012 ). However, studies predicting HE have predominantly focused on the characteristics of the hematoma itself ( Morotti et al, 2020 ; Jiang et al, 2022 ), often overlooking the contributory role of PHE. A previous study suggested that reduced cerebral blood volume in the perihematomal region is associated with HE, suggesting a potential role for the perihematomal region in the pathophysiology of HE ( Morotti et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested that PHE formation, inflammation, and HE are linked ( Alvarez-Sabín et al, 2004 ; Silva et al, 2005 ; Florczak-Rzepka et al, 2012 ). However, studies predicting HE have predominantly focused on the characteristics of the hematoma itself ( Morotti et al, 2020 ; Jiang et al, 2022 ), often overlooking the contributory role of PHE. A previous study suggested that reduced cerebral blood volume in the perihematomal region is associated with HE, suggesting a potential role for the perihematomal region in the pathophysiology of HE ( Morotti et al, 2019b ).…”
Section: Discussionmentioning
confidence: 99%
“…Compared to traditional visual assessments, radiomics analysis offers comprehensive, objective, and quantitative evaluations. A recent meta-analysis has shown the efficacy of radiomics features extracted from CT images in characterizing the heterogeneity of ICH and predicting HE (Jiang et al, 2022). Additionally, emerging evidence has indicated a strong correlation between the CT-based radiomics features of PHE and functional prognosis (Huang et al, 2022(Huang et al, , 2023.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, the four radiologists performed at a median sensitivity of 84.5% for each tumor type and a median specificity of 61.8, 80.6, and 50.0%. Accordingly, radiomics is emerging as a potential tool to predict HE in patients with sICH ( 13 ). In the present review, we examine the current status and future of radiomics in HE detection and sICH management.…”
Section: Introductionmentioning
confidence: 99%